WRITTEN IMAGES: STUDENT-GENERATED DRAWING FOR EXPERIENTIAL LEARNING IN A TRANSNATIONAL EDUCATION PARTNERSHIP - Stuart Burch (PUPIL: International Journal of Teaching, Education and Learning, 2026)
Purpose: Research suggests drawing to be a valuable learning strategy. However, most adults claim they “can’t draw.” This article advances ways of navigating this challenge in the context of a transnational UK-China university partnership. Approach: An action research, autoethnographic case study into the planning and implementation of accessible drawing strategies featuring observation and reflection on the development and evaluation of an experiential, identity-focused drawing initiative. Findings: Overcoming anxieties among “non-artists” confirms drawing to be a popular and effective means of exploring identities, especially when combined with a formative, spoken presentation. Originality: Observational findings demonstrate that “drawing to learn” has broad applicability for “problem-posing education” (Freire). The ability to visualise direct personal experiences enhances a sense of selfhood and an appreciation of the identities of others. The account of this is original in being a research-informed, experience-based enquiry that features student feedback and reflection.